Porphyrin-phthalocyanine/pyridylfullerene supramolecular assemblies - Pereira, Ana M. V. M.; Hausmann, Anita; Tome, Joao P. C.; Trukhina, Olga; Urbani, Maxence; Neves, Maria G. P. M. S.; Cavaleiro, Jose A. S.; Guldi, Dirk Michael; Torres, Tomas (Chemistry - A European Journal, 2012)
The synthesis and photophysical properties of several porphyrin (P)-phthalocyanine (Pc) conjugates (P-Pc; 1-3) are described, in which the phthalocyanines are directly linked to the β-pyrrolic position of a meso-tetraphenylporphyrin. Photoinduced energy- and electron-transfer processes were studied through the preparation of H P-ZnPc, ZnP-ZnPc, and PdP-ZnPc conjugates, and their assembly through metal coordination with two different pyridylfulleropyrrolidines (4 and 5). The resulting electron-donor-acceptor hybrids, which were formed by axial coordination of compounds 4 and 5 with the corresponding phthalocyanines, mimicked the fundamental processes of photosynthesis; that is, light harvesting, the transduction of excited-state energy, and unidirectional electron transfer. In particular, photophysical studies confirmed that intramolecular energy-transfer resulted from the S excited state as well as from the S excited state of the porphyrins to the energetically lower-lying phthalocyanines, followed by an intramolecular charge-transfer to yield P-Pc ·C . This unique sequence of processes opens the way for solar-energy-conversion processes. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.